Exploring the antioxidant and antimicrobial properties of five indigenous Kenyan plants used in traditional medicine - Virginia Gichuru; Irene Sbrocca; Michela Molinari; Teodora Chiara Tonto; Vittoria Locato; Sara Cimini; Laura De Gara (Scientific Reports)
Abstract Defined by the World Health Organization (WHO) as indigenous knowledge and practices used for maintaining health and treating illnesses, traditional medicine (TM) represents a rich reservoir of ancient healing practices rooted in cultural traditions and accumulated wisdom over centuries. Five indigenous Kenyan plant species traditionally used in African TM, named Afzelia quanzensis, Azadirachta indica, Gigasiphon macrosiphon, Grewia bicolor, and Lannea schweinfurthii, represent a valuable resource in healing practices, yet their chemical composition and bioactivity remain understudied. To depict a primary bio-chemical characterization of these plants, their antioxidant and antimicrobial features have been evaluated by the use of methods validated in this context. G. bicolor, and G. macrosiphon were found to have great potential as sources of bioactive metabolites, such as chlorophyll a (1456.29 µg/ g DW; 1104.33 µg/ g DW), chlorophyll b (712.48 µg/ g DW; 443.31 µg/ g DW), and carotenoids (369.71 µg/ g DW; 300 µg/ g DW) as well as phenols (31.78 mg GAE/g DW; 27.54 GAE/g DW), and exhibiting high antioxidant activity, according to TEAC, DPPH and FRAP assays. Additionally, L. schweinfurthii and G. macrosiphon demonstrated antimicrobial activity against the Gram-negative bacteria E. coli, as well as against Gram-positive ones, S. aureus and B. subtilis.